Surgeon directed transcranial motor evoked potential spinal cord monitoring in spinal deformity surgery: A review of viability, safety and efficacy - Magampa, Ramanare (Division of Orthopaedic Surgery, 2021)
Aims Spinal deformity surgery carries the risk of neurological injury. Neurophysiological monitoring allows early identification of intraoperative cord injury facilitating early intervention which has a better prognosis. Although multimodal monitoring is the ideal, resource constraints make surgeon directed intra-operative transcranial motor evoked potential (TcMEP) monitoring a useful compromise. Our experience using surgeon directed TcMEP is presented in terms of viability, safety and efficacy. Methods A retrospective review was performed on a single surgeon's prospectively maintained database from 2010 to 2017 where TcMEP monitoring was utilised. The upper limbs were used as the control. A true alert was recorded when there was a 50% or more loss of amplitude of the lower limbs with maintained upper limb signals. Patients with true alerts were identified and their case history analysed. Results Of the 299 cases were reviewed, 279 (93.3%) had acceptable traces throughout and awoke with normal clinical neurological function. No case with normal traces had a post-operative clinical neurological deficit. True alerts occurred in 20 (6.7%) cases. The alert group diagnoses included adolescent idiopathic scoliosis 9 (45%) and congenital scoliosis 6 (30%). The incidence of deterioration based on diagnosis AIS was 9/153 (6%), congenital 6/30 (20%) and TB spine 2/16 (12.5%). Deterioration in congenital is much more common (p=0.02) when compared to AIS. 65% of alerts occurred during rod instrumentation and 15% during decompression of the internal apex in vertebral column resection surgery. 4 (20%) alert cases awoke with clinically detectable neurological compromise Conclusion Surgeon directed TcMEP monitoring has a 100% negative predictive value and allows early identification of physiological cord distress and immediate intervention. In resource constrained environments, surgeon directed TcMEP is a viable and effective method of intra-operative spinal cord monitoring. Clinical relevance • Surgeon directed TcMEP monitoring has a 100% negative predictive value. • In resource constrained environments, surgeon directed TcMEP is viable and effective • Level 3 evidence